Creation and development of the local information computer network of Institute of High Energy Physics and Nuclear Physics NSC KIPT - Dudnik, V.A.; Krivorukov, E.V.; Kudrjavtsev, V.I.; Sereda, T.M.; Us, S.A.; Shestakov, M.V. (Вопросы атомной науки и техники, 2005)
Results and the basic stages of creation and development of local information computer network at Institute of
High Energy Physics and Nuclear Physics NSC KIPT for last five years are submitted. The purpose of work was
increase of an overall performance of researchers due to rational use of resources and creation on base local
information computer network of shared system. In article obtained experience and specificity of realization of such
systems is reflected. Представлено результати й основні етапи створення і розвитку локальної інформаційної обчислювальної
мережі Інституту фізики високих енергій і ядерної фізики ННЦ ХФТІ за останні п'ять років. Метою роботи
було підвищення ефективності праці дослідників за рахунок раціонального використання ресурсів і
створення на базі локальної інформаційної обчислювальної мережі системи колективного користування. У
статті описано накопичений досвід і специфіка реалізації таких систем. Представлены результаты и основные этапы создания и развития локальной информационной
вычислительной сети Института физики высоких энергий и ядерной физики ННЦ ХФТИ за последние пять
лет. Целью работы было повышение эффективности работы исследователей за счет рационального
использования ресурсов и создание на базе локальной информационной вычислительной сети системы
коллективного пользования. В статье описывается накопленный опыт и специфика реализации таких систем.